2020
DOI: 10.3390/pathogens9020079
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Leishmania

Abstract: Leishmania are obligate intracellular parasites known to have developed successful ways of efficient immunity evasion. Because of this, leishmaniasis, a disease caused by these flagellated protists, is ranked as one of the most serious tropical infections worldwide. Neither prophylactic medication, nor vaccination has been developed thus far, even though the infection has usually led to strong and long-lasting immunity. In this paper, we describe a “suicidal” system established in Leishmania mexicana, a human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The authors stated that such a deliberately attenuated parasite may be used to vaccinate the host, because its viability is controlled by toxin stabilization, resulting in a significantly reduced pathogenesis. 28 Evaluation of α-toxin IC 50 in our study showed that there is a significant difference between the mean number of amastigotes from 100 macrophages in groups exposed to α-toxin plus glucantime in comparison with negative control. As the strong fatal effect of the two mentioned components on cultivated Leishmania parasites was found at lower optimal concentrations (0.03 ± 0.002 µg/mL) compared with glucantime plus non-toxic α-toxin or each of them alone.…”
Section: Discussionmentioning
confidence: 60%
“…The authors stated that such a deliberately attenuated parasite may be used to vaccinate the host, because its viability is controlled by toxin stabilization, resulting in a significantly reduced pathogenesis. 28 Evaluation of α-toxin IC 50 in our study showed that there is a significant difference between the mean number of amastigotes from 100 macrophages in groups exposed to α-toxin plus glucantime in comparison with negative control. As the strong fatal effect of the two mentioned components on cultivated Leishmania parasites was found at lower optimal concentrations (0.03 ± 0.002 µg/mL) compared with glucantime plus non-toxic α-toxin or each of them alone.…”
Section: Discussionmentioning
confidence: 60%
“…So, a PLA2 from B. jararacussu venom encapsulated in liposomes displays therapeutic effectiveness comparable to that of known antiparasitic Glucantime in a cutaneous leishmaniasis mouse model [ 70 ]. A fairly original construct has been developed based on the expression of a PLA2 from the B. pauloensis venom in a leishmanial “suicidal” strain, which leads to the inducible death of the parasite cells in vitro [ 71 ]. The approach that also should be mentioned here is to identify in the toxin molecule the fragments of amino acid sequence responsible for interaction with the target in protozoa, followed by the synthesis of these relatively short peptides and their further use as antiprotozoals.…”
Section: Discussionmentioning
confidence: 99%
“…Promastigotes and amastigotes are physiologically different in their sensitivity to drugs, with amastigotes having the greater capability to accumulate drugs [75]. Furthermore, Podešvová et al [52] reported that variations in the compositions of parasite membranes could also be responsible for the differences in the activities of snake venoms and their fractions. Additionally, mechanisms including post-translational modifications, protein stability, and folding may likely influence toxin activity on parasites [52].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Borges et al [29] and Borges et al [30] reported that PLA2s of B. pauloensis inhibited parasite adhesion, intracellular proliferation, parasite viability, intracellular proliferation and proinflammatory cytokine production in T. gondii. Furthermore, the PLA2s of B. pauloensis induced in vitro cell death in L. mexicana [52], and Zieler et al [72] reported that the PLA2s of C. adamanteus blocked the ookinete adhesion and oocyst formation of both P. gallinaceum and P. falciparum. According to a previous study [63], crotoxin B and its complex from C. durissus cumanensis exerted a cytotoxic effect against the mononuclear cells of P. falciparum, and another [19] reported that the crovirin from C. viridis could inhibit and lyse humaninfective trypanosome species, including the intracellular amastigotes.…”
Section: Antiprotozoal Effect Of Snake Venom Components or Fractionsmentioning
confidence: 99%
See 1 more Smart Citation